Case Report: Esophageal cancer under comprehensive treatment strategy—application and clinical outcome analysis of combined immunotherapy, targeted therapy, and low-dose radiotherapy - Yanling Yuan; Xingxi Pan; Lihua Tong; Wanming He; Wen Yang (Frontiers in Oncology)
Current evidence for the combined use of immunotherapy, low-dose chemoradiotherapy, and epidermal growth factor receptor-targeted therapy for the treatment of advanced esophageal squamous cell carcinoma is lacking. We report the case of a 73-year-old woman with squamous cell carcinoma of upper middle thoracic esophagus. After undergoing concurrent chemoradiotherapy combined with immunotherapy and anti-angiogenic targeted therapy, the patient achieved a progression-free survival of 17 months. To date, the patient has achieved 35 months of overall survival, which continues to extend, with a good quality of life. Immunotherapy combined with low-dose concurrent chemoradiotherapy is a promising option for elderly patients with advanced esophageal cancer who are intolerant to standard treatments. The addition of an epidermal growth factor receptor monoclonal antibody as a radiosensitizer improves therapeutic efficacy. The combination of sintilimab and anlotinib has the potential to treat recurrent and metastatic esophageal cancer. Tailoring treatment strategies for specific patient groups is essential in personalized medicine.